Towards Enhancing Linguistic Proficiency in Maritime Education: A Study of Cadets' Perspectives at the Maritime Institute Jakarta - Marudut Bernadtua Simanjuntak (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
This research delves into the perspectives of 240 Semester 3 cadets at the Maritime Institute Jakarta (STIP Jakarta) regarding the establishment of a standardized maritime language for effective communication at sea. Employing a qualitative descriptive approach, the study integrates document analysis and self-administered surveys to unravel the nuanced dynamics of linguistic proficiency in the maritime context. The findings reveal a perceived gap between academic training and practical linguistic challenges, prompting recommendations for the integration of simulated scenarios and immersive training methods into the curriculum. Motivation emerges as a critical influencer of linguistic competences, necessitating a paradigm shift in linguistic training methodologies that connect linguistic development to the broader narrative of professional identity. Anticipation of communication challenges during internships highlights the immediate need for industry-responsive linguistic training. Collaborative efforts between educational institutions and industry stakeholders, along with the incorporation of real-world examples, are recommended to enhance the preparedness of cadets for diverse communication scenarios in their professional roles. This study contributes nuanced insights to the discourse on maritime education, emphasizing the need for a dynamic and experiential approach to linguistic training that aligns with the evolving demands of the maritime industry. The identified themes and recommendations provide a roadmap for curriculum enhancement and pedagogical refinement, ensuring that maritime education remains responsive and effective in preparing cadets for the complexities of real-world communication at sea.